2012
DOI: 10.3748/wjg.v18.i17.2112
|View full text |Cite
|
Sign up to set email alerts
|

Association of NOD1 and NOD2 genes polymorphisms withHelicobacter pylorirelated gastric cancer in a Chinese population

Abstract: Genetic polymorphisms in NOD1 and NOD2 may interact with H. pylori infection and may play important roles in promoting the development of gastric cancer in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 35 publications
2
39
1
Order By: Relevance
“…For example, rs2066842 (P268S) has been reported to be a risk variant for GC in Polish and German populations, but we could not analyze this SNP due to poor cluster separation of its genotypes . Moreover, rs3135500 has been reported to increase the risk for GC in the Chinese population, a finding not confirmed by us . Nevertheless, according to the haploview analysis of CEU HapMap population, the haplotype inversely associated with GC in our study carries the wild‐type or major variants of these two polymorphisms.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…For example, rs2066842 (P268S) has been reported to be a risk variant for GC in Polish and German populations, but we could not analyze this SNP due to poor cluster separation of its genotypes . Moreover, rs3135500 has been reported to increase the risk for GC in the Chinese population, a finding not confirmed by us . Nevertheless, according to the haploview analysis of CEU HapMap population, the haplotype inversely associated with GC in our study carries the wild‐type or major variants of these two polymorphisms.…”
Section: Discussioncontrasting
confidence: 66%
“…10,11 Moreover, rs3135500 has been reported to increase the risk for GC in the Chinese population, a finding not confirmed by us. 32 Nevertheless, according to the haploview analysis of CEU HapMap population, the haplotype inversely associated with GC in our study carries the wild-type or major variants of these two polymorphisms. In an Italian population, rs2066844 and rs5743293 were also reported to increase susceptibility to GC, but these SNPs are not included in the HapMap version we used.…”
Section: Discussionmentioning
confidence: 49%
“…There are several studies which demonstrated that the polymorphisms of the NOD1 (nucleotide-binding oligomerization domain) and NOD2 genes in different populations were related to variant clinical outcomes of H pylori infection. Moreover, it was shown that NOD1 and NOD2 genes polymorphisms and/or mutation induced the incidence of gastric carcinoma in different populations, in recently reports (Wang et al, 2012;Zhang et al, 2012). The risk for the development of gastric cancer in patients with a family history of gastric cancer has been reported to be as high as 1.6-2.6 folds (Kondo et al, 2003;Kawasaki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotide-binding oligomerization domain 1 (NOD1) receptor, is a relatively recently described cytosolic PRR known to execute important functions in the immune system (Girardin et al, 2001, Ogura et al, 2001) by recognizing a wide range of microbes bearing the specific meso-diaminopimelic acid (meso-DAP) moiety and mediating the corresponding inflammatory response to these infectious agents (Carneiro et al, 2004). Not only is NOD1 important in host defense and autoimmune diseases, but recently, it has also been implicated in tumorigenesis for a number of cancers, including gastric cancer (Wang et al, 2012), head and neck carcinomas (Millrud et al, 2013), oral squamous cell cancer (Wang et al, 2014), prostate adenocarcinoma (Kang et al, 2012), and lung cancer (Ozbayer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%